2013
DOI: 10.1186/1742-4690-10-110
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the human immunodeficiency virus type 2 envelope in the first years of infection is associated with the dynamics of the neutralizing antibody response

Abstract: BackgroundDifferently from HIV-1, HIV-2 disease progression usually takes decades without antiretroviral therapy and the majority of HIV-2 infected individuals survive as elite controllers with normal CD4+ T cell counts and low or undetectable plasma viral load. Neutralizing antibodies (Nabs) are thought to play a central role in HIV-2 evolution and pathogenesis. However, the dynamic of the Nab response and resulting HIV-2 escape during acute infection and their impact in HIV-2 evolution and disease progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 70 publications
0
17
0
Order By: Relevance
“…Together with the observation that within-host viral lineages leading to transmission events evolve approximately half as fast as other lineages [ 7 ], these findings build a consistent picture of different rates of evolution for HIV-1 within- and between-hosts, for all of the subtypes that have been analyzed, and across the whole genome. Intriguingly, similar mismatches in evolutionary rates are observed for HIV-2, Hepatitis B, and Hepatitis C viruses [ 27 , 43 47 ], leading us to speculate that such mismatches are a general feature of rapidly evolving chronic viral infections in humans.…”
Section: Discussionmentioning
confidence: 75%
“…Together with the observation that within-host viral lineages leading to transmission events evolve approximately half as fast as other lineages [ 7 ], these findings build a consistent picture of different rates of evolution for HIV-1 within- and between-hosts, for all of the subtypes that have been analyzed, and across the whole genome. Intriguingly, similar mismatches in evolutionary rates are observed for HIV-2, Hepatitis B, and Hepatitis C viruses [ 27 , 43 47 ], leading us to speculate that such mismatches are a general feature of rapidly evolving chronic viral infections in humans.…”
Section: Discussionmentioning
confidence: 75%
“…The rates of evolution and positive selection were twice as high in the first child compared to the second child. At the age of 5 years, the CD4 percentage decreased to 25% in the second child and despite antiviral therapy viral load was not controlled and the child died of AIDS aged 9 years [89]. The authors concluded that the lack of nAb activity may have contributed to the poor outcome of the second child, but because of the rarity of vertically acquired HIV-2 infection, it is hard to generalize from these data.…”
Section: Hiv-1 and Hiv-2 Env Diversification And Associated Clinical mentioning
confidence: 95%
“…In a study by Rocha et al the evolution of HIV-2 envelope under the selective pressure of nAbs was compared from the early stages of the HIV-2 infection in two patients with different clinical outcomes [89]. They followed HIV-2 evolution from acute to chronic stages of infection in two children infected by vertical transmission (a relatively rare event, estimated to occur at a frequency of 0-4%).…”
Section: Hiv-1 and Hiv-2 Env Diversification And Associated Clinical mentioning
confidence: 99%
“…In this review, we focus on engineering bNAbs against HIV-1 infection but much can be learned from natural HIV-2 humoral immunity. At the level of the infected individual, HIV-2 Env evolves at equivalent/faster rates than HIV-1 [40, 41], likely due to selective pressure from NAb responses [42]. Antigenic differences allowing for the greater generation of NAb responses in HIV-2 as compared to HIV-1 include greater stability of the Env trimer [43], less glycan shielding and a more ‘open’ conformation allowing for greater accessibility of NAb epitopes [36, 44], and greater structural and functional constraints to diversity in some NAb epitopes as compared to HIV-1 [45].…”
Section: Introductionmentioning
confidence: 99%